PENDAMPINGAN MASYARAKAT TANGGAP BENCANA DAN PENYERAHAN BANTUAN KE MASYARAKAT CIANJUR - Sularso Budilaksono; Yudi Yulius; Sri Astuti Indriyati; Nana Trisnawati; Maya Syafriana Effendi; Shafenti Shafenti; Siti Komsiah; Nafisah Yuliani (LPPM Universitas Bina Bangsa, 2022)
The earthquake that occurred in Cianjur brought the impact of damage and casualties both died, wounded and collapsed residences. Assistance to the disaster response community is carried out by providing material assistance for the renovation of damaged school buildings, assistance for basic daily needs and the construction of MCK or public bathrooms for earthquake victims in Cianjur in three villages, namely Limbangsari Village, Cikancana Village, Gekbrong District and Warung Kondang Village. The refugee community received assistance in the form of donations of basic food equipment and equipment for daily life which was given directly by the head of the foundation and the Rector of Universitas Persada Indonesia YAI. Solving problems from the implementation of PKM, namely the community has benefited and been helped in completing the renovation of school buildings in accordance with the needs of the community. The results of the questionnaire also found that partner satisfaction was almost an average of 85% very satisfied with the implementation of community service (PKM) for the implementation of beneficiaries, the construction of bathrooms and school renovations